Differential effects of olive oil, soybean oil, corn oil and lard oil on carbon tetrachloride-induced liver fibrosis in mice. Issue 10 (11th October 2019) - Gao, Yanan; Li, Xuguang; Gao, Qiang; Fan, Li; Jin, Haobin; Guo, Yueping
Abstract: Olive oil could attenuate carbon tetrachloride (CCl4 ) induced liver fibrosis (LF) in mouse model. The present study aimed to evaluate the effects of other common oils on CCl4 induced LF. Healthy male ICR mice were administered with CCl4 intraperitoneally at 2.5 ml/kg twice a week for total 3 weeks. Mice were pre-treated with olive oil, soybean oil, corn oil or lard oil. After treatment, histopathological changes were observed using Masson trichrome staining, and alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA), hydroxyproline (HYP) and triglyceride (TG) were measured by commercial kits. The expression of LF related genes was detected by quantitative real-time PCR. We found that soybean oil or olive oil significantly reduced ALT and AST levels in serum, and MDA, HYP and TG levels in the liver, compared with corn oil or lard oil. Moreover, Masson trichrome staining and real-time PCR showed that the mice treated with CCl4 dissolved in soybean oil or olive oil had less fibrosis and apoptosis in the liver comparted to the mice treated with CCl4 dissolved in corn oil or lard oil. In conclusion, soybean oil but not corn or lard oil exerts protective effects against CCl4 induced LF in mice, possibly due to its antioxidant activity.